Simulation of A Solar Drier for Iroko Wood (Chlorophora Excelsa) in A Tropical Environment - Fesa Putra Kristianto; Mercusuar Kemall Gibran Salim (Eksergi, 2023)
In a previous study conducted by Simo Tagne to designing a solar dryer based on mathematical equations for iroko wood in Cameroon, Africa. However, there is no complete simulation of the drying process on the tool, resulting in the lack of detailed elaboration of the iroko wood drying process. The purpose of this study is to simulate in detail the drying process on the tool using an ANSYS simulation. The model used in this simulation still uses the same mathematical model that has been studied before. This research begins by setting up the ANSYS application with the previous mathematical model, environmental conditions, and tool specifications. Furthermore, simulations are carried out using the ANSYS application with measurements of pressure, temperature, velocity and mass transfer. From this simulation obtained results for the distribution of pressure, temperature, velocity, and mass transfer. From all these distributions, it is sufficient to describe the drying process of the tool according to the mathematical model that has been studied previously.